2021
DOI: 10.5038/2640-6489.6.2.1173
|View full text |Cite
|
Sign up to set email alerts
|

The perceived impact of COVID-19 pandemic on healthcare cost in Bangladesh

Abstract: The study showed the effect of the COVID-19 pandemic on healthcare expenses including the price of medicines, protective equipment, medical devices, healthcare facilities, and food. A self-administered questionnaire was used as the data collection tool and 400 people from different Bangladesh divisions (Dhaka, Chittagong, Barisal, Khulna, Mymensingh, Rajshahi, and Sylhet) participated in this study. Multiple regression analysis was used to estimate the impact of independent variables on dependent variables. R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…More specifically, the framework argues that the three proposed drivers or stimuli of social media advertising (i.e., entertainment, interaction, and e-WOM) interact to both brand image and consumers' intention to purchase. This assertion is supported by similar studies in the field (Seo and Park, 2018;Işık et al, 2024a;Islam et al, 2022;Işık et al, 2024b;Dehghani et al, 2015;Islam et al, 2024;Bilgin, 2018;Algharabat, 2017;Rana et al, 2023;Islam et al, 2020;Godey et al, 2016;Islam et al, 2021). Within this context, Seo and Park (2018) and Bilgin (2018) found that entertainment and interaction significantly influence the brand image of products in social media advertising, and e-WOM also exerts a noteworthy impact on these components (Godey et al, 2016).…”
Section: Theoretical Background and Hypotheses Developmentsupporting
confidence: 56%
“…More specifically, the framework argues that the three proposed drivers or stimuli of social media advertising (i.e., entertainment, interaction, and e-WOM) interact to both brand image and consumers' intention to purchase. This assertion is supported by similar studies in the field (Seo and Park, 2018;Işık et al, 2024a;Islam et al, 2022;Işık et al, 2024b;Dehghani et al, 2015;Islam et al, 2024;Bilgin, 2018;Algharabat, 2017;Rana et al, 2023;Islam et al, 2020;Godey et al, 2016;Islam et al, 2021). Within this context, Seo and Park (2018) and Bilgin (2018) found that entertainment and interaction significantly influence the brand image of products in social media advertising, and e-WOM also exerts a noteworthy impact on these components (Godey et al, 2016).…”
Section: Theoretical Background and Hypotheses Developmentsupporting
confidence: 56%
“…The study focuses on the signi cant occurrences the industry experienced during the study period, namely the pandemic scenario. Due to corona pandemic, the price of the all type of product increased according to Islam et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic scenario is the center of the study, which examines the industry's important events over the study period. According to Islam et al, (2021) the price of all products went up because of the corona pandemic. Another study conducted by Sha qullah and Rahman (2021), the study looked at how the rate of in ation and unemployment has increased while the rate of GDP growth, industrial output, and investment have all dramatically decreased.…”
Section: To Analyze the Association Between Unemployment Rate And Ban...mentioning
confidence: 99%